Epigenetic valleys in the Tikves Basin in the Republic of Macedonia - Kole Pavlov; Ace Milenkovski; Gjorgi Pavlovski; Ivan Radevski (UTMS Journal of Economics, 2014)
The epigenetic valleys as part of the fluvial relief are of special geomorphologic significance. As ostensibly anomalous phenomena, they mirror the inconsistent fluvial relief, i.e. a phase of adjustment of longitudinal profiles of rivers. The subject of research in this paper involved some forms of the fluvial relief in the drainage basin of the Vardar River, in the Tikves Basin, which had some predispositions to be classified as an epigenetic valleys. The necessary geological-and-lithological and morphological parameters have shown that specific segments in the river valleys in Tikves are distinguished by special physiognomy, lithology and genesis, which correspond to epigenetic valleys and gorges. Thus arguments indicated in total ten created epigenetic valleys and gorges on the level of the Tikves Basin. Seven epigenetic occurrences were formed below the neogene level, whereas three of them were formed above the neogene level.
Keywords: Q5; 330; epigenetic valley; epigenetic gorge; epigenetic incision; river relief